STRATEGI PEMBANGUNAN ISLAM DENGAN ADANYA PERANAN DIGITAL EKONOMI - Nur Fadilah (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2024)
The digital system, as a concept, lacks universal agreement, yet it is inseparable from the changes shaping modern life. The rapid advancement of digital systems has become pivotal in providing feedback to individuals, communities, and nations. In today’s digital era, many developments are rooted in Western civilization, particularly the digital economy, which has brought widespread benefits such as prosperity, convenience, and comfort. However, the influence of technology is deeply intertwined with societal dynamics and can lead to both positive and negative outcomes, requiring users to exercise caution and wisdom in its use. In the economic realm, digital systems are integral to shaping strategies and methods. Despite this, many Islamic economic development strategies struggle to keep pace with rapid digital advancements. This raises critical questions: Can Islamic economics contribute to the advancement of digital systems? Can it adapt and align with digital progress to achieve significant development? These challenges represent pressing issues for the Islamic economic framework today. Thus, the role of a well-defined Islamic Economic Development Strategy, aligned with digital systems, is essential to address these complexities.